Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah Dalam Pembayaran PBB Kota Pekanbaru Via ATM Dan E_Mobile Bank Riau Kepri Syariah - Herman, Herman; Kurniawan, Teuku Reza (Eko dan Bisnis: Riau Economic and Business Review, 2023)
The purpose of this research is to determine the Influence of Service Quality on Customer Satisfaction in Paying Property Tax (PBB) in Pekanbaru City via ATM and E_Mobile Bank Riau Kepri Syariah. To achieve this objective, a study was conducted with a sample of 90 people, using a simple random sampling method. The data analysis method used simple linear regression. Based on the results of the partial t-test, it was found that service quality has a significant influence on customer satisfaction, as evidenced by the t-test value being greater than the t-table value (12.537 > 1.987). The magnitude of the influence of the service quality variable on customer satisfaction is 0.641 (64.1%), as confirmed by the results of the determination test, which obtained an R2 value of 0.641. Recommendations that can be suggested include encouraging Bank Riau Kepri Syariah to continue promoting the use of ATM and e_mobile applications for property tax (PBB) payments in Pekanbaru City to its customers.